Penerapan Analisis SWOT Terhadap Keberlangsungan Usaha di Butik Shifa Olshop Medan - Zahratunnisa Zahratunnisa Zahratunnisa; Muhammad Rahmat Rahmat (Syntax Idea, 2022)
This study aims to determine the application of SWOT analysis on business continuity at the Shifa Olshop Boutique Medan. This study uses key informants, namely the owner, 3 employees and 8 customers. The tool used in developing the strategy is a SWOT analysis. SWOT analysis is used to find out what strategy is used after looking at the strengths, weaknesses, opportunities and threats that the Shifa Olshop Boutique has obtained from the interviews. The results of this study found that the internal factor that became a strength in business continuity at the Shifa Olshop boutique was having good quality raw materials. Meanwhile, the internal factor that becomes the weakness of business continuity at the Shifa Olshop boutique is the limited skills of the production employees. Also, the external factor that becomes an opportunity for business continuity at the Shifa Olshop boutique is a location that can be reached by customers who directly shop at the store or order online with low delivery costs because the distance is not so far. Meanwhile, the external factor that poses a threat to business continuity at the Shifa Olshop boutique is price competition with competitors.